Acute myeloid leukaemia relapsing after allogeneic haemopoietic stem cell transplantation: prognostic factors and impact of initial therapy of relapse. Issue 3 (6th March 2018) - Lim, Andrew B. M.; Curley, Cameron; Fong, Chun Y.; Bilmon, Ian; Beligaswatte, Ashanka; Purtill, Duncan; Getta, Bartlomiej; Johnston, Anne M.; Armytage, Tasman; Collins, Marnie; Mason, Kate; Fielding, Katherine; et al.
Abstract: Background/Aims: We sought to determine factors associated with the overall survival from relapse (OSR) of acute myeloid leukaemia (AML) after allogeneic haemopoietic stem cell transplantation (alloHSCT) and the effect of first salvage therapy and subsequent graft‐versus‐host disease (GVHD) on OSR. Methods: Data on 386 patients from nine Australian centres with relapsed AML post‐alloHSCT were collected retrospectively. OSR was calculated using the Kaplan–Meier method. Univariate and multivariate analyses were conducted using the log‐rank test and proportional hazards modelling, respectively and a prognostic index for OSR was derived from multivariate modelling. Results: On multivariate analysis, relapse within 6 months (hazard ratio (HR) 2.4, P  < 0.001) and grade 3–4 acute GVHD preceding relapse (HR 2.0, P  = 0.004), were associated with inferior OSR. Patients with 1–2 factors had inferior OSR compared to those with zero factors (all patients: HR 2.3, P  < 0.001, patients given salvage: HR 1.8, P  < 0.001). The first salvage therapy used post‐relapse was donor cell therapy (DCT) (second alloHSCT or donor lymphocyte infusion) in 75, re‐induction chemotherapy (CT) in 103, radiotherapy in 8 and interferon‐α in 6. Although re‐induction CT death rate was low (2%), survival after CT was inferior to DCT (HR 1.9, P  < 0.001). No survival benefit was seen for patients who developed GVHD following salvage therapy ( P  = 0.405). Conclusion: Patients with AML who relapse beyond 6 months from alloHSCT without prior grade 3–4 acute GVHD have a better outcome from salvage therapy. Salvage treatments employing DCT as the initial treatment of AML relapse confer a survival advantage over CT.